Model Pembelajaran Pendidikan Agama Islam Berbasis Humanistik Dalam Pengembangan Karakter Mandiri Peserta Didik. - Soleh Alihudin (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2024)
The purpose of this research was conducted to determine the implementation of the PAI learning model, its impact on the development of independent character of students and the influential factors of students'development.The method used for this research is a qualitative method with a descriptive approach. As for the data sources, the researcher uses observation, interviews, and documentation. The researcher conducted researches that gained the results on making the teacher some arrangements before starting the lesson by determining the learning objectives first, followed by identifying the initial abilities of the students, preparing the topics and their relevant media such as using the Jigsaw type cooperative learning model and the methods of lecture, discussion, and also question and answer. factor of students' independence which are the internal and external factors. The impacts of its implementation are students feel happy, enthusiastic, dare to express their opinions, confident, creative and able to establish good cooperation.Â